Characterisation of porous silicon field emitter properties - Boswell, E; Huang, M; Smith, G; Wilshaw, P (IEEE, 1995)
The field emission properties and structure of silicon field emitter tips, covered with a porous silicon layer have been studied. The emission from porous silicon emitters with a variety of morphologies, thicknesses and substrate types have been investigated using both an adapted scanning electron microscope and a field ion/field emission microscope. It has been found that the points of emission for p-type and n-type porous silicon have larger field enhancement factors and smaller emission areas than for non-porous emitters, which is consistent with the presence of sharp surface asperities. Field emission is shown to originate at the porous surface rather than at the bulk silicon/porous silicon interface. Bright and dark field transmission electron microscope (TEM) analysis has been carried out on the samples. E or p- and n-type material this has indicated a core within the emitter tip which is crystalline and covered with the surrounding amorphous porous silicon. This core has an improved aspect ratio (over the original emitter shape) and a rough, silicon/porous silicon interface is observed.